PD-L1 expression in microvascular endothelial cells predicts the efficacy and side effects of anlotinib - Yingfang Feng; Yuan Gao; Shaochuan Liu; Tingting Qin; Yan Zhang; Jing Wang; Kai Li (Frontiers in Oncology)
BackgroundImmunotherapy plays a crucial role in the treatment of tumors. However, few studies have investigated the relationship between the expression of Programmed Cell Death Ligand 1 (PD-L1, CD274) in microvascular endothelial cells (MECs), including blood endothelial cells (BECs) and lymphatic endothelial cells (LECs), and immune cell infiltration within tissues.MethodsIn our study, we utilized data from The Cancer Genome Atlas, a mouse subcutaneous xenograft model, and immunofluorescence and immunohistochemical staining to investigate the relationship between PD-L1 expression in melanoma MECs at different tumor stages and the infiltration of CD8+ T cells in tumor and normal organs, under conditions with and without anlotinib treatment.ResultsWe found that PD-L1 expression was upregulated in tumor MECs, while anlotinib downregulated PD-L1 expression in both tumor and normal tissue MECs, corresponding with increased infiltration of CD8+ T cells in the tissues. Additionally, the antitumor effect of anlotinib was most pronounced when administered during the mid-stage of tumor development.ConclusionsThis study evaluated the most effective timing for anlotinib to downregulate PD-L1 expression in tumor and normal tissues to promote immune infiltration. Our findings may offer valuable insights for the clinical use of anlotinib and its potential side effects.